2004
DOI: 10.1016/s0006-3495(04)74372-6
|View full text |Cite
|
Sign up to set email alerts
|

Mean-Square Displacement Relationship in Bioprotectant Systems by Elastic Neutron Scattering

Abstract: Neutron intensity elastic scans on trehalose, maltose, and sucrose/H(2)O mixtures as a function of concentration, temperature, and exchanged wave vector are presented. The experimental findings show a crossover in molecular fluctuations between harmonic and anharmonic dynamical regimes. A new operative definition for the degree of fragility of glass-forming systems is furnished by using explicitly the connection between viscosity and mean-square displacement. The procedure is tested for the investigated mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
101
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 44 publications
14
101
1
Order By: Relevance
“…The interpretative model to describe the observed behavior can be visualized as follows for the elementary flow process (the α-relaxation): an atom jumps in the fast processes (β-relaxation motions) with a Gaussian probability distribution characterized by a mean-square amplitude <u 2 > loc , defined as the difference between the mean square displacement of the ordered and disordered phase [15]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interpretative model to describe the observed behavior can be visualized as follows for the elementary flow process (the α-relaxation): an atom jumps in the fast processes (β-relaxation motions) with a Gaussian probability distribution characterized by a mean-square amplitude <u 2 > loc , defined as the difference between the mean square displacement of the ordered and disordered phase [15]:…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that a linear relationship between M M and m exists [15]. On the basis of the relationships introduced, we will try now to get information on the fragility degree of the glassy systems which when host proteins are present show an Intensity (a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) allows also a very intuitive understanding of the effect of different instrumental time resolution on the usually explored apparent MSD measured at ω = 0 (see also Ref. [4,14]):…”
Section: Dependence Of Umentioning
confidence: 99%
“…Well-known examples include the dynamics in glass-forming systems [1][2][3] and bioprotectant disaccharides [4] as well as the protein dynamical transition [5,6], in particular the coupling of protein dynamics to the environment [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%